It IS worth the effort: Patient knowledge of reproductive aspects of inflammatory bowel disease improves dramatically after a single group education session. (1st August 2014) - Mountifield, Réme; Andrews, Jane M.; Bampton, Peter
Abstract: Background: Individuals with Inflammatory Bowel Disease (IBD) have poor knowledge regarding the implications of disease for fertility and pregnancy. Previous studies suggest that this poor knowledge adversely influences reproductive decision making. Aim: To examine the effect of a single group education session on IBD-specific reproductive knowledge in subjects with IBD. Method: People with IBD attending an educational event were invited to complete the CCPKnow questionnaire, testing reproductive knowledge in IBD, before and after an evidenced based presentation on this topic delivered by a Gastroenterologist. Results: Of 248 attendees, 155 participated; 69% female, mean age 40.3 years. CCPKnow scores (maximum 17) were low at baseline and increased significantly post education (mean 5.4 pre vs. 14.5 post education; p < 0.0001). A large majority (65.1%) of subjects had "poor" (score < 8) knowledge at baseline, compared with only 1.9% after education (p < 0.0001). Whilst all subareas of knowledge improved after education, the most important improvement was in attitudes toward medication use in pregnancy: 33.5% of subjects indicated at baseline that women should avoid all drugs in pregnancy compared with only 1.2% post education (p < 0.0001). Conclusion: A single group-delivered education event focussed on reproductive issues in IBD can dramatically improve patient knowledge. This has the potential to change reproductive behaviour and may reduce voluntary childlessness resulting from misperceptions amongst individuals with IBD.